Perancangan Sistem Aplikasi Pengambilan Keputusan Pemilihan Media Promosi Menggunakan Unifed Modelling Language - Lidya Wati; Rezki Kurniati; Mansur Mansur (Ikatan Ahli Informatika Indonesia, 2018)
Small and medium enterprises (SMEs) in Bengkalis Subdistrict have not been maximized in utilizing information technology to increase sales of products owned. This is due to the lack of utilizing media promotion, lack of knowledge of business people about information technology and limited market access. According to the results of direct observations to several business actors in Bengkalis Regency, product marketing was carried out by entrusting products to food and mini-market stores in Bengkalis Regency. This study aims to build a decision-making system for the selection of SMEs in Bengkalis Regency by using the Unified Modeling Language design model, which consists of Use Case Diagrams, Activity Diagrams and Sequence Diagrams. In determining the decision to determine the right promotional media the method used is Fuzzy Mamdani, which consists of five criteria, namely promotion costs, duration, place, market segment, and ad scale. While alternatives as decisions are television, radio, newspapers, internet and pamphlets. The result of the research is an application designed to help SMEs in determining what promotion media is the best so as to increase marketing and income Keywords:Unified Modelling Language, Desicion Support System, Fuzzy Mamdani, Media Promotion, SMEs